The Effect Of Company Growth, Bankruptcy Risk, Audit Opinion, And Company Size On Delays In Financial Reporting By Property Companies On The Indonesian Stock Exchange - Usama, Leny Nazila; Subekti, Imam (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study analyzes the effect of company growth, bankruptcy risk, audit opinion, and company size on the financial reporting delay of property companies listed on the Indonesia Stock Exchange (IDX) during 2019–2022. The data used in this research are secondary in the form of audited annual financial reports. A total of 180 samples were obtained using a non-participant observation method. Logistic regression analysis examined the relationship between the independent and dependent variables. The results indicate that company growth and bankruptcy risk do not significantly affect reporting delays. In contrast, audit opinion has a negative and significant effect, suggesting that an unqualified audit opinion reduces the likelihood of delayed reporting. Company size also has a considerable impact, indicating that larger companies tend to report their financial statements more punctually. These findings imply the crucial role of auditors and firm characteristics in promoting timely financial reporting as a form of transparency for investors and other stakeholders.